Beguines of Languedoc — “other” Beguines and the cult of their saints - Yu. V. Rodionova (Российский журнал истории Церкви)
The religious movement of the Beguines in Languedoc in the first quarter of the XIV century is a unique phenomenon of the development of the ideology of spirituals — ideology that arose within Franciscanism. Using his example, it is possible to clearly trace how the ideology of educated intellectuals, who developed it and discussed it within their own order, passed to groups of representatives of the urban population. The new adherents of the teaching developed it within the framework of their idea of how a “classical” religious movement should be built — their own saints, martyrs, martyrologies and holy relics appeared. In Western historiography, in the presence of a large amount of collected material, the activities of individuals who have left written evidence of the development of the doctrine of the Holy Spirit are actively studied, however, there is no connection between how these ideas were practically introduced into the minds of people far from intellectual disputes and their development within urban population groups.